Late Posthemorrhagic Structural and Functional Changes in Pulmonary Circulation Arteries - S. A. Andreyeva; V. T. Dolgikh (Общая реаниматология, 2008)
Objective: to reveal the major regularities and mechanisms of morphological changes in the rat pulmonary circulation arteries in the late posthemorrhagic period and to compare them with age-related features of the vessels. Materials and methods: experiments to generate graduated hemorrhagic hypotension with the blood pressure being maintained at 40 mm Hg were carried out on young (5—6-month) albino male Wistar rats. Throughout hypotension and 60 days after blood loss, the blood was tested to determine low and average molecular-weight substances by spectrophotometry and the pro- and antioxidative systems by chemiluminescence. Pulmonary circulation arteries were morphologically studied in young animals, rats in the late posthemorrhagic period and old (24—25-month) rats. Results. Sixty-minute hemorrhagic hypotension leads to the development of endotoxemia and imbalance of the pro- and antioxidative systems, the signs of which are observed in the late periods (2 months) after hypotension. At the same time, the posthemorrhagic period is marked by the significant pulmonary circulation arterial morphological changes comparable with their age-related alterations in old rat. This shows up mainly in the reorganization of a connective tissue component in the vascular wall: the elevated levels of individual collagen fibers, their structural changes, elastic medial membrane destruction and deformity. At the same time, there is a change in the morphometric parameters of vessels at all study stages while their lowered flow capacity is only characteristic for intraorgan arteries. Conclusion: The increased activity of free radical oxidation and endotoxemia may be believed to be one of the causes of morphological changes in pulmonary circulation arteries in the late posthemorrhagic period, which is similar to age-related vascular alterations. Key words: hemorrhagic hypotension, pulmonary circulation arteries, free radical oxidation, endotoxemia, remodeling, late posthemorrhagic period, age-related vascular changes.